Respuesta :
Answer:
1.
Step-by-step explanation:
-3x6y4/-3x6y4
The top of the fraction is exactly the same as the bottom
So the answer is 1.
For this case we must simplify the following expression:
[tex]\frac {-3x ^ 6y ^ 4} {- 3x ^ 6y ^ 4} =[/tex]
The signs "-" are canceled, then:
[tex]\frac {3x ^ 6y ^ 4} {3x ^ 6y ^ 4} =[/tex]
In this case, it is observed that we have a unitary fraction, which by definition is that which has the numerator equal to the denominator.
Example:
[tex]\frac {a} {a} = 1[/tex]
So:
[tex]\frac {3x ^ 6y ^ 4} {3x ^ 6y ^ 4} = 1[/tex]
Answer:
1